Fractionated bipolar radiofrequency and bipolar radiofrequency potentiated by infrared light for treating striae: A prospective randomized, comparative trial with objective evaluation. Issue 3 (12th January 2016) - Harmelin, Yona; Boineau, Dominique; Cardot‐Leccia, Nathalie; Fontas, Eric; Bahadoran, Philippe; Becker, Anne‐lise; Montaudié, Henri; Castela, Emeline; Perrin, Christophe; Lacour, Jean‐Philippe; Passeron, Thierry
Abstract : Background and Objective: Very few treatments for striae are based on prospective randomized trials. The objective of this study was to assess the efficacy of bipolar fractional radiofrequency and bipolar radiofrequency potentiated with infrared light, alone or combined, for treating abdominal stretch marks. Study Design/Materials and Methods: Bicentric prospective interventional randomized controlled trial in the department of Dermatology of University Hospital of Nice and Aesthetics Laser Center of Bordeaux, France. Men and women of age 18 years or above, who presented for the treatment of mature or immature abdominal striae were included. The patients' abdomens were divided into four equal quadrants. Bipolar radiofrequency potentiated with infrared light and fractional bipolar radiofrequency were applied, alone or combined, and compared to the remaining untreated quadrant. The main criterion of evaluation was the measurement of depth of striae, using 3D photography at 6 months follow‐up. A global assessment was also rated by the physician performing the treatment and by the patients. Histological analysis and confocal laser microscopy were additionally performed. Results: A total of 22 patients were enrolled, and 384 striae were measured. In per protocol analysis mean striae depth was decreased by 21.64%, observed at 6 months follow‐up with the combined approach, compared to an increase of 1.73% in the control group ( P  < 0.0001). No significant difference in striae width was observed between the treated or control quadrants. Global assessment by the physician who performed the treatment and by the patient both showed greater improved with the combination treatment compared to control areas ( P  = 0.004 and P  = 0.01, respectively). A more homogeneous interlacing pattern and thicker collagen fibers with a decreased proportion of elastic fibers was observed after treatment. Conclusion: Fractional bipolar radiofrequency, combined with bipolar radiofrequency potentiated by infrared light, is an effective treatment of both immature and mature striae of the abdomen. Lasers Surg. Med. 48:245–253, 2016. © 2016 Wiley Periodicals, Inc.